Comparing the reactivity of alkynes and alkenes on silicon 100 surfaces - Ng, A.; Ciampi, Simone; James, M.; Harper, J.; Gooding, J. (American Chemical Society, 2009)
The relative reactivities of alkynes to alkenes on hydrogen-terminated silicon (100) surfaces, under conditions where a monolayer will be produced via hydrosilylation, were measured using two different approaches. The first approach was to form monolayers from a series of solutions containing different mole fractions of an alkyne, with a trifluorothioacetate distal moiety and an alkene with a terminal carboxylic acid functional. X-ray photoelectron spectroscopic analysis of the resultant surfaces showed that the mole fraction of alkyne on the surface was larger than that in the respective alkyne/alkene mixture. By fitting the XPS data, we estimated that the reactivity ratio of alkyne to alkene was approximately 1.7 ± 0.2 when monolayers were formed at 120 °C. The second approach was using a molecule containing both an alkyne at one end and an alkene at the other, non-1 -yne-8-ene, as the hydrosilylation reagent such that either end could attach to the silicon surface. The relative orientation of this molecule, once reacted with a hydrogen-terminated Si(1OO) surface, was determined by coupling an additional reagent to the distal end of the monolayer. The reagent used was azidoferrocene, which could attach onto free alkyne moieties on the surface only via the 1,3-Huisgen cycloaddition "click" reaction. Electrochemical analysis was then used to determine how many ferrocene moieties were attached to the SAM surface. In this way, it was shown that the alkyne end reacted preferentially with the silicon surface compared with the alkene end. The reactivity ratio of the alkyne end to the alkene end was increased from 2.0 ± 0.2 to 9 ± 1 when the temperature was decreased from 120 to 65 °C. © 2009 American Chemical Society.